Diamonds in nature a guide to rough diamonds - Tappert, Ralf; Tappert, Michelle C.; SpringerLink (Online service). (Heidelberg [Germany] New York Springer, 2011)
Diamonds in Nature: A Guide to Rough Diamonds illustrates and explains the unique properties of natural diamonds, such as their crystal shapes, colors, surface textures, and mineral inclusions. It also contains up-to-date information about the origin and scientific significance of diamonds. With more than 200 high-quality photographs and drawings, it is an invaluable reference for the professional geoscientist and anyone with an interest in diamonds.
1. The origin of diamonds -- 2. The morphologies and shapes of diamonds -- 3. The colors of diamonds -- 4. The surface texture of diamonds -- 5. Inclusions in diamonds and their geological meaning.
Electronic reproduction.
Keywords: Diamonds; Diamonds -- Pictorial works; Diamonds -- Grading; Crystallography; Diamonds -- Inclusions; Electronic books